Comparative analysis of the motherhood gap in employment and wages: The role of family policies and their interaction - Ewa Cukrowska-Torzewska (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2016)
The paper documents employment and wage gaps, which arise between mothers and childless women, for a set of 28 European countries. The role of family policies in explaining these inequalities is then examined by looking at a single policy as well as childcare and leave policies interaction. The findings from the fixed effects model reveal that childcare coverage for small children and the length of maternity and paid parental leaves are important for explaining the size of the motherhood gap in employment. The impact of the leaves depends, however, on childcare availability: long maternity leaves combined with high childcare coverage lead to greater employment gap than when the coverage is low. The results do not prove that the interaction effect is present for the motherhood wage gap, which is found to be predominantly affected by the length of paid parental leave.
Keywords: J13; J18; J22; J31; 330; family gap; maternal employment; family policies; childcare